2021
DOI: 10.1017/s0022215121002243
|View full text |Cite
|
Sign up to set email alerts
|

Hear me out: rethinking internal auditory meatus magnetic resonance imaging in primary care. A cohort evaluation

Abstract: Background Imaging detects acoustic neuroma, a rare pathology associated with asymmetric sensorineural hearing loss and tinnitus, that is mostly managed conservatively. Scanning indication is debatable, without evaluation in primary care, despite the high burden of audiovestibular symptoms and commissioning of general practitioner imaging. Method Cohort evaluation of two years' internal auditory meatus magnetic resonance imaging in primary care. Results Of 200 scans req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Three studies (13,18,20) documented and reported exclusively on patients with nonpulsatile tinnitus only. Only one of the studies documented symptom duration (14) at the time of investigation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies (13,18,20) documented and reported exclusively on patients with nonpulsatile tinnitus only. Only one of the studies documented symptom duration (14) at the time of investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The largest study included in our review (13) had 566 patients, and 24% had incidental findings on MRI IAM. Another study (14) reported that these incidental findings led to unnecessary onward referrals and patient distress without any resultant significant diagnosis or change in care. This represents a significant concern given the unnecessary distress and adverse effect on patients’ well-being it can cause.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations